Relationship between L^p convergence and a.e. convergence

It turns out that convergence in Lp implies that the norms converge. Conversely, a.e. convergence and the fact that norms converge implies Lp convergence. Amazing!

Relationship between L^p convergence and a.e. convergence:
Let f, \{f_k\}\in L^p, 0<p\leq\infty. If \|f-f_k\|_p\to 0, then \|f_k\|_p\to\|f\|_p. Conversely, if f_k\to f a.e.\ and \|f_k\|_p\to\|f\|_p, 0<p<\infty, then \|f-f_k\|_p\to 0. Note that the converse may fail for p=\infty.

Proof:
Assume \|f-f_k\|_p\to 0.

(Case: 0<p<1).
Lemma 1:
If 0<p<1, |a+b|^p\leq|a|^p+|b|^p for all a,b\in\mathbb{R}.
Proof of Lemma 1:
\displaystyle 1=\frac{|a|}{|a|+|b|}+\frac{|b|}{|a|+|b|}\leq\left(\frac{|a|}{|a|+|b|}\right)^p+\left(\frac{|b|}{|a|+|b|}\right)^p=\frac{|a|^p+|b|^p}{(|a|+|b|)^p}.
Hence |a+b|^p\leq(|a|+|b|)^p\leq|a|^p+|b|^p.
End Proof of Lemma 1.
Hence, using |a|^p\leq|a-b|^p+|b|^p and |b|^p\leq|a-b|^p+|a|^p we see that \displaystyle ||a|^p-|b|^p|\leq|a-b|^p.

Thus
\begin{aligned}  \left|\|f_k\|_p^p-\|f\|_p^p\right|&=\left|\int(|f_k|^p-|f|^p)\right|\\  &\leq\int\left||f_k|^p-|f|^p\right|\\  &\leq\int|f_k-f|^p\\  &=\|f-f_k\|_p^p\to 0\ \ \ \text{as}\ k\to\infty.  \end{aligned}

Hence \|f_k\|_p\to\|f\|_p.

(Case: 1\leq p\leq\infty.)

By Minkowski’s inequality, \|f\|_p\leq\|f-f_k\|_p+\|f_k\|_p and \|f_k\|_p\leq\|f-f_k\|_p+\|f\|_p so that \displaystyle \left|\|f_k\|_p-\|f\|_p\right|\leq\|f-f_k\|_p\to 0 as k\to\infty. Done.

Converse:

Assume f_k\to f a.e.\ and \|f_k\|_p\to\|f\|_p, 0<p<\infty.
Lemma 2:
For a,b\in\mathbb{R}, |a+b|^p\leq 2^{p-1}(|a|^p+|b|^p) for 1\leq p<\infty.
Proof of Lemma 2:
By convexity of |x|^p for 1\leq p<\infty, \displaystyle \left|\frac 12 a+\frac 12 b\right|^p\leq\frac 12 |a|^p+\frac 12 |b|^p.
Multiplying throughout by 2^p gives \displaystyle |a+b|^p\leq 2^{p-1}(|a|^p+|b|^p).

Thus together with Lemma 1, for 0<p<\infty we have |f-f_k|^p\leq c(|f|^p+|f_k|^p) with c=\max\{2^{p-1}, 1\}.

Note that |f-f_k|^p\to 0 a.e.\ and \phi_k:=c(|f|^p+|f_k|^p)\to\phi:=2c|f|^p a.e.\ which is integrable. Also, \int\phi_k\to\int\phi since \|f_k\|_p^p\to\|f\|_p^p. By Generalized Lebesgue’s DCT, we have \int |f-f_k|^p\to 0 thus \displaystyle \|f-f_k\|_p\to 0.

(Show that the converse may fail for p=\infty):

Consider f_k=\chi_{[-k,k]}\in L^\infty(\mathbb{R}). Then f_k\to f a.e.\ where f(x)\equiv 1, and \|f_k\|_\infty\to\|f\|_\infty=1. However \|f-f_k\|_\infty=1\not\to 0.

Advertisements

About mathtuition88

http://mathtuition88.com
This entry was posted in math and tagged , . Bookmark the permalink.

Leave a Reply

Fill in your details below or click an icon to log in:

WordPress.com Logo

You are commenting using your WordPress.com account. Log Out / Change )

Twitter picture

You are commenting using your Twitter account. Log Out / Change )

Facebook photo

You are commenting using your Facebook account. Log Out / Change )

Google+ photo

You are commenting using your Google+ account. Log Out / Change )

Connecting to %s